Strain Rate Effect on Mechanical Properties of the 3D-Printed Metamaterial Foams With Tunable Negative Poisson’s Ratio - Gao, Di; Wang, Bin; Gao, Haoqiang; Ren, Fuguang; Guo, Chunxia; Ma, Shuai; Cao, Tiewa; Xia, Yu; Wu, Yansen (Frontiers in Materials, 2021)
As a kind of metamaterial, the negative Poisson’s ratio foams, which expand (shrink) in the transverse direction when stretched (compressed) in the longitudinal direction, have many potential applications in fields such as aerospace and mechanical and biomedical engineering. In this paper, the out-of-plane crushing behaviors of four types of the orthogonal isotropic NPR convex-concave foams (CCF) were extensively studied using an electronic universal testing machine and Instron machine at different strain rates where each test was conducted at a constant compressive velocity under uniaxial compression. Strain rate effect on mechanical properties of these foams is experimentally studied. When the strain rate increases, the compressive force enhancement of the foams is obvious and varies with different specimens. The difference in energy absorption and deformation patterns for these foams between quasi-static and dynamic loading conditions is also analyzed. We find that the deformation patterns for the specimens are not only related to the compressive velocities but also the topologies of the specimens. The research in this paper is expected to be meaningful for the optimization design of the foam structures/materials widely used in the fields of aerospace and mechanical and biomedical engineering.